Semantic Choice in Translation from Morris’ Modern Semiotic Theory - Gao, Fan (Technium Social Sciences Journal, 2024)
From the perspective of the Internet, this article focuses on semantic selection in translation, and delves into the semantic selection of translation in Morris’s modern semiotic theory. After exploring the relevant theoretical concepts by dimensions, it is found that the semantics of translation in Morris’ modern semiotic theory can be divided into three types: denotational semantics, pragmatic semantics and intra-verbal semantics. Finally, the choice of the three types of semantics: denotational semantics, pragmatic semantics and intra-verbal semantics is explored in depth to provide guidance for related theoretical research.